Peran Kualitas Kelekatan Anak dengan Orangtua pada Keterampilan Sosial Remaja - Adijanti Marheni; I Rustika Made; Luh Kadek Pande Ary Susilawati (Universitas Andalas, 2018)
This research aimed to examine correlation between child-parent attachement and social skills in adolescent. Social skill is one of important parts in adolescent development, because adolescents are trying to build relationship beyond the family. One of the factors affecting social skills development among adolescent is the quality of attachment between child and parent. Hypothesis in this research stated that there is a correlation between child-parent attachment and adolescent’s social skills. Participants in this research were 164 high school students in Denpasar. Instruments used in this research were Social Skills Scale (α = 0,831) and Indonesian translated version of Inventory of Parent and Peer Attachment (α = 0,941). The Result of this study showed positive correlation between the quality of child-parent attachment and adolescent’s social skills (r=0,323, p<0,05). This result reflected the significant effort to improve the quality of attachment between child and parents in adolescence, with the result that adolescent will build good social skills.